Collusion under different pricing schemes - Florian Gössl; Alexander Rasch (Journal of Economics & Management Strategy, 2020)
We analyze collusive outcomes under different pricing schemes in a differentiated product market in which customers have elastic demand. Starting with a situation in which firms can set two-part tariffs to price discriminate, we consider two policy interventions that ban price discrimination: Firms must set (a) linear prices or (b) fixed fees. We find that collusion at maximum prices becomes harder to sustain under linear prices. By contrast, the analysis shows that the fixed fees policy facilitates collusion at maximum prices. The results have important implications for competition policy.
Keywords: 330